Role of Hepcidin as A Predictor for Iron Metabolism Disorders and Inflammation in Stage 4 Chronic Kidney Disease Patient with Anemia - Mohammad Abbas Sobh , Hala Mostafa Kamel Imam , Mohamed Ismail Seddik , Deiaa Eldein Massoud Sadek (Cuestiones de Fisioterapia, 2025)
Background: Anemia is more frequent in cases with chronic kidney disease compared to the general population. Aim: To assess the role of hepcidin as a predictor for iron metabolism disorders in stage 4 CKD cases with anemia and to evaluate the role of hepcidin as a predictor for inflammation in stage four chronic kidney disease cases with anemia. Patients and methods: This case-control cross-sectional observational research has been conducted on 64 cases with CKD stage 4 with anemia divided into four groups: Group (A): involved 16 cases with hemoglobin levels below 6 g/dl; Group (B): included 16 cases with hemoglobin concentrations six to nine gram per deciliters; Group (C): included 16 patients with hemoglobin levels above 9-11 g/dl; and Group (D): included 16 healthy subjects as a control group at the Nephrology Unit of the InternalMedicine Department in Assiut University Hospitals from April 2020 till July 2022. Results: Utilizing the ROC curve, it has been demonstrated that hepcidin may be utilized to discriminate among anemic groups and the control group at a cutoff level of > 6.6 ng/ml, with 100% specificity, 93.7% sensitivity, 100% PPV, and 94.07% NPV (p-value < 0.001 & AUC = 0.996). Conclusion:Hepcidin was a good predictor for iron metabolism disorders and inflammation in stage 4 CKD patients with anemia. Hepcidin and CRP levels were the highest among patients with Hgb levels below 6 gm/dl. Hepcidin level correlated positively with the increase of ferritin in all patients.